2015
DOI: 10.1038/ncomms7894
|View full text |Cite
|
Sign up to set email alerts
|

C-Nap1 mutation affects centriole cohesion and is associated with a Seckel-like syndrome in cattle

Abstract: Caprine-like Generalized Hypoplasia Syndrome (SHGC) is an autosomal-recessive disorder in Montbéliarde cattle. Affected animals present a wide range of clinical features that include the following: delayed development with low birth weight, hind limb muscular hypoplasia, caprine-like thin head and partial coat depigmentation. Here we show that SHGC is caused by a truncating mutation in the CEP250 gene that encodes the centrosomal protein C-Nap1. This mutation results in centrosome splitting, which neither affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 39 publications
2
38
0
2
Order By: Relevance
“…One of its major components is c-Nap1 (alias CEP250) (32), which serves as anchoring points for rootletin, Cep68 and LRCC45 that form the thin filaments of the linker (33, 34). Loss of function of each of these proteins leads to premature centriole splitting (32)(33)(34)(35). However, we showed that Ift52 did not colocalized with c-Nap1 ( Figure 5B) and immunostainings of c-Nap1, rootletin, Cep68 and LRCC45 did not reveal any obvious defects of localisation of these proteins to the centrosome in Ift52 -/cells compared to control cells ( Figure S3C-E).…”
Section: Ift52 -/Cells Exhibit Centriole Splittingmentioning
confidence: 87%
“…One of its major components is c-Nap1 (alias CEP250) (32), which serves as anchoring points for rootletin, Cep68 and LRCC45 that form the thin filaments of the linker (33, 34). Loss of function of each of these proteins leads to premature centriole splitting (32)(33)(34)(35). However, we showed that Ift52 did not colocalized with c-Nap1 ( Figure 5B) and immunostainings of c-Nap1, rootletin, Cep68 and LRCC45 did not reveal any obvious defects of localisation of these proteins to the centrosome in Ift52 -/cells compared to control cells ( Figure S3C-E).…”
Section: Ift52 -/Cells Exhibit Centriole Splittingmentioning
confidence: 87%
“…Mutations in the human homolog of C - Nap1 , called CEP250 or CEP2 , are associated with Usher syndrome, a disease characterized by retinitis pigmentosa and hearing loss [ 55 ]. In cattle, mutations in C - Nap1 are associated with microcephaly, suggesting that the linker between mother and daughter centrioles plays important roles in neural development in mammals [ 56 ].…”
Section: Murine Basal Body Structurementioning
confidence: 99%
“…Le gain de cette approche réside surtout dans la petite fraction à séquencer par rapport au génome total et donc au coût plus limité par échantillon, autorisant à travailler sur un nombre bien plus élevé d'échantillons. Cette technologie a été utilisée en 2010 pour la caractérisation de l'anomalie SHGC en race Montbéliarde (Floriot et al 2015). Elle a comme difficulté essentielle le temps et le travail nécessaires pour dessiner les oligonucléotides de capture, ainsi que le coût de leur synthèse qui ne se justifie que si le nombre d'échantillons à traiter est important.…”
Section: / Recherche De Mutations Candidates Par Séquençage Du Génomeunclassified